Are flood basalt eruptions monogenetic or polygenetic? - SHETH, HC; CANON-TAPIA, E (International Journal of Earth Sciences, 2015)
A fundamental classification of volcanoes divides them into "monogenetic" and "polygenetic." We discuss whether flood basalt fields, the largest volcanic provinces, are monogenetic or polygenetic. A polygenetic volcano, whether a shield volcano or a stratovolcano, erupts from the same dominant conduit for millions of years (excepting volumetrically small flank eruptions). A flood basalt province, built from different eruptive fissures dispersed over wide areas, can be considered a polygenetic volcano without any dominant vent. However, in the same characteristic, a flood basalt province resembles a monogenetic volcanic field, with only the difference that individual eruptions in the latter are much smaller. This leads to the question how a flood basalt province can be two very different phenomena at the same time. Individual flood basalt eruptions have previously been considered monogenetic, contrasted by only their high magma output (and lava fluidity) with typical "small-volume monogenetic" volcanoes. Field data from Hawaiian shield volcanoes, Iceland, and the Deccan Traps show that whereas many feeder dykes were single magma injections, and the eruptions can be considered "large monogenetic" eruptions, multiple dykes are equally abundant. They indicate that the same dyke fissure repeatedly transported separate magma batches, feeding an eruption which was thus polygenetic by even the restricted definition (the same magma conduit). This recognition helps in understanding the volcanological, stratigraphic, and geochemical complexity of flood basalts. The need for clear concepts and terminology is, however, strong. We give reasons for replacing "monogenetic volcanic fields" with "diffuse volcanic fields" and for dropping the term "polygenetic" and describing such volcanoes simply and specifically as "shield volcanoes," "stratovolcanoes," and "flood basalt fields.".